2019
DOI: 10.1016/j.jaci.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific changes in the molecular phenotype of patients with moderate-to-severe atopic dermatitis

Abstract: Background: Atopic dermatitis (AD) shows differential clinical presentation in older compared with younger patients. Nevertheless, changes in the AD molecular profile with age are unknown. Objective: We sought to characterize age-related changes in the AD profile. Methods: We evaluated age-specific changes in lesional and nonlesional tissues and blood from patients with moderate-tosevere AD (n 5 246) and age-matched control subjects (n 5 71) using immunohistochemistry, quantitative real-time PCR, and Singulex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 73 publications
6
114
2
2
Order By: Relevance
“…In addition, the results start to define age-specific differences between pediatric patients with AD and age-matched control subjects as a complement to our recent data showing differences between elderly versus young AD adult endotypes. 3 Our data suggest that even adolescents have a different profile from adults, possibly contributing to the somewhat lower response to the recently approved IL-4 receptor a antagonist dupilumab in adolescents versus adults. 30,31 Immune responses at birth are immature, 10 with decreases in frequencies of naive T cells in healthy children with increasing age paralleled by increases in Tcm/Tem cell counts.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In addition, the results start to define age-specific differences between pediatric patients with AD and age-matched control subjects as a complement to our recent data showing differences between elderly versus young AD adult endotypes. 3 Our data suggest that even adolescents have a different profile from adults, possibly contributing to the somewhat lower response to the recently approved IL-4 receptor a antagonist dupilumab in adolescents versus adults. 30,31 Immune responses at birth are immature, 10 with decreases in frequencies of naive T cells in healthy children with increasing age paralleled by increases in Tcm/Tem cell counts.…”
Section: Discussionmentioning
confidence: 68%
“…83 Additionally, AD has a highly varied endotype repertoire, with different immune polarizations. 3,84,85 Despite common features, particularly increased T H 2 expression, AD is endotypically different across ages, and treatments should be tailored to the unique age endotype. Although one could hypothesize that the immune changes merely reflect developmental phenomena that are age related, the lack of clear clustering in control subjects implicates AD as the driver of the distinct, progressive, age-related endotypic characteristics rather than age alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly AD, phenotypic analyses of peripheral blood cytokine concentrations demonstrated the dominance of a Th2 cytokine profile, i.e., IL-4, IL-5, and IL-13, in older patients with IgE-allergic AD, whereas dominance of a Th1 cytokine profile, i.e., IFN-γ, was observed in older patients with AD and low serum total IgE levels [6]. In a recent study on age-specific changes in the molecular phenotype of patients with AD, serum total IgE levels and eosinophil counts were negatively correlated with age in patients with AD, and patients with elderly AD tended to show immune skewing with decreased Th2 and Th22 cytokines and increased Th1 cytokines in lesional skin compared with patients with adult AD [9]. The participation and role of allergen-specific IgEs in the development of skin lesions of AD has been controversial [26], but immunohistopathological analysis in our previous studies indicated that, at least in patients with IgE-allergic elderly AD, IgE-mediated allergic inflammation (composed of IgE-bearing cells, including mast cells, dermal dendritic cells, inflammatory dendritic epidermal cells, and Langerhans cells) accompanied by specific allergens (e.g., HDMs) play a critical role in the features of skin lesions [7,16,21].…”
Section: Histopathology and Pathophysiology Of Skin Lesionsmentioning
confidence: 97%
“…However, the paradigm has recently changed. The number of cases of AD remaining or first appearing in adulthood [4,5], and even in older adults [3,6], have increased and the characteristics of elderly AD have become apparent [7][8][9][10]. Hence, this newly defined subgroup of elderly AD (age > 60 or ≥ 60 years) was recently added into the classification of AD as a fourth subtype [11,12].…”
Section: Introductionmentioning
confidence: 99%